Clinical characteristics and risk factors for kidney failure in patients with autosomal dominant polycystic kidney disease: A retrospective study. Issue 47 (25th November 2022) - Park, Hanil; Paek, Jin Hyuk; Kim, Yaerim; Park, Woo Yeong; Han, Seungyeup; Jin, Kyubok
Abstract : Autosomal dominant polycystic kidney disease (ADPKD) is a hereditary and progressive renal disease. By the age of 65 years, 45% to 70% of patients with ADPKD reach end-stage renal disease (ESRD). Although there are various treatments for this condition, no standard therapy exists to delay the progression of ADPKD. Hence, understanding the factors that affect disease progression may be helpful for the treatment of ADPKD. The medical records of 288 patients with ADPKD at Keimyung University Dongsan Medical Center between January 1989 and August 2018 were analyzed retrospectively. Furthermore, we inspected the risk factors involved in the progression of ADPKD and the kidney survival rates of patients using the Cox proportional hazards model and Kaplan–Meier survival analysis. The mean age at the time of diagnosis was 43.1 ± 14.1 years, and there were 146 males (50.7%). In total, 197 patients (68.4%) had hypertension and 11 patients (3.8%) had cerebral aneurysm. Stroke occurred in 35 patients (12.1%), including 11 cases of cerebral hemorrhage and 24 cases of cerebral infarction. Twenty-eight patients (9.7%) died during the follow-up period (117.1 ± 102.1 months). Infection (42.9%) was the most common cause of mortality, followed by sudden cardiac death (25.0%). Overall, 132 patients (45.8%) progressed to ESRD and 104 patients (36.1%) required renal replacement therapy (RRT). The mean duration from diagnosis to RRT was 110.8 ± 93.9 months. Age at diagnosis after 30 years (odd's ratio [OR], 2.737; 95% confidence interval [CI], 1.320–5.675; P  = .007), baseline serum creatinine levels (OR, 1.326; 95% CI, 1.259–1.396; P  < .001), and cyst infection (OR, 2.065; 95% CI, 1.242–3.433; P  = .005) were the independent risk factors for kidney failure in multivariable analysis. To delay the advance of ADPKD to ESRD, early diagnosis and close observation for the onset of cyst infection are crucial.